2021
DOI: 10.3390/cells10113096
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Hyaluronan in Barrier Alteration-Related Disease

Abstract: In skin, although the extracellular matrix (ECM) is highly developed in dermis and hypodermis, discrete intercellular spaces between cells of the living epidermal layers are also filled with ECM components. Herein, we review knowledge about structure, localization and role of epidermal hyaluronan (HA), a key ECM molecule. HA is a non-sulfated glycosaminoglycan non-covalently bound to proteins or lipids. Components of the basal lamina maintain some segregation between the epidermis and the underlying dermis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 126 publications
(198 reference statements)
0
11
0
Order By: Relevance
“…Several studies reported that HA-based transdermal delivery systems exhibit excellent biocompatibility, enhanced permeability, and efficient localized release of topical anti-inflammatory drugs, inhibiting eczema-associated skin inflammation [ 39 ]. Moreover, the bioactive effect of hyaluronic acid in filling the intercellular spaces of the living epidermal layers is well known, highlighting its role in the treatment of AD pathology [ 40 ]. These properties, alongside the enhanced controlled release abilities, improved targeting capacity to the skin strata, and easy manipulation of swelling level [ 41 ], make HA gels efficient devices for topical drug delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported that HA-based transdermal delivery systems exhibit excellent biocompatibility, enhanced permeability, and efficient localized release of topical anti-inflammatory drugs, inhibiting eczema-associated skin inflammation [ 39 ]. Moreover, the bioactive effect of hyaluronic acid in filling the intercellular spaces of the living epidermal layers is well known, highlighting its role in the treatment of AD pathology [ 40 ]. These properties, alongside the enhanced controlled release abilities, improved targeting capacity to the skin strata, and easy manipulation of swelling level [ 41 ], make HA gels efficient devices for topical drug delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Among these isoenzymes, HAS3 is very active and is responsible for synthesizing low molecular weight polymers; there is significant mRNA expression of HAS3 in healthy keratinocytes. 16,17 Epidermal ceramides, mainly accounted for by acyl-ceramides, are crucial for skin barrier function. They are secreted from stratum granulosum cells to form a part of the cornified envelope and create sheets of lipid lamellae, resulting in an impenetrable barrier in the SC.…”
Section: Introductionmentioning
confidence: 99%
“…LMW HA (MW < 10 K Da) was found to stimulate the migration and proliferation of endothelial cells, promote the synthesis of collagen, 15 and upregulate inflammatory mediators. While, HMW HA (MW > 1000 K Da) was reported to inhibit the production of pro‐inflammatory mediators, 16‐19 decrease oxidative stress, and inhibit angiogenesis 20‐22 . In addition, chemically modified HA, such as acetylated HA (AcHA), shows better bioavailability than normal HA, 23 being able to decrease MMP expression and slow down ECM degradation induced by chronobiological and extrinsic aging 24 …”
Section: Introductionmentioning
confidence: 99%
“…While, HMW HA (MW > 1000 K Da) was reported to inhibit the production of pro-inflammatory mediators, [16][17][18][19] decrease oxidative stress, and inhibit angiogenesis. [20][21][22] In addition, chemically modified HA, such as acetylated HA (AcHA), shows better bioavailability than normal HA, 23 being able to decrease MMP expression and slow down ECM degradation induced by chronobiological and extrinsic aging. 24 However, the co-effect of GHK-Cu and HA was rarely reported.…”
mentioning
confidence: 99%